Acute Declines in Estimated Glomerular Filtration Rate in Patients Treated With Benazepril and Hydrochlorothiazide Versus Amlodipine and Risk of Cardiovascular Outcomes - Elaine Ku; Kenneth Jamerson; Timothy P. Copeland; Charles E. McCulloch; Hocine Tighiouart; Mark J. Sarnak (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Acute declines in estimated glomerular filtration rate (eGFR) occur commonly after starting angiotensin‐converting enzyme inhibitors. Whether declines in eGFR that occur after simultaneously starting angiotensin‐converting enzyme inhibitors with other antihypertensive agents modifies the benefits of these agents on cardiovascular outcomes is unclear. Methods and Results We identified predictors of acute declines in eGFR (>15% over 3 months) during randomization to benazepril plus amlodipine versus benazepril plus hydrochlorothiazide in the ACCOMPLISH (Avoiding Cardiovascular Events through Combination Therapy in Patients Living with Systolic Hypertension) trial. We then determined the relation between declines in eGFR (treated as a binary variable, ≤15% versus >15% and separately, as a restricted spline variable) and the composite risk of fatal and nonfatal cardiovascular events using Cox proportional hazards models. We included 10 714 participants (median age 68 years [Q1 63, Q3 73]), of whom 1024 reached the trial end point over median follow‐up of 2.8 years. Predictors of acute declines in eGFR>15% over 3 months included assignment to hydrochlorothiazide (versus amlodipine) and higher baseline albuminuria. Overall, declines in eGFR ≥15% (versus <15%) were associated with a 26% higher hazard of cardiovascular outcomes (95% CI, 1.07–1.48). In spline‐based analysis, risk for cardiovascular outcomes was higher in the hydrochlorothiazide arm at every level of decline in eGFR compared with the same magnitude of eGFR decline in the amlodipine arm. Conclusion Combined use of benazepril and amlodipine remains superior to benazepril and hydrochlorothiazide for cardiovascular outcomes, regardless of the magnitude of the decline in eGFR that occurred with initiation of therapy.